Phalangopsidae crickets from the Indian Region (Orthoptera, Grylloidea), with the descriptions of new taxa, diagnoses for genera, and a key to Indian genera - Desutter-Grandcolas, Laure; Jaiswara, Ranjana (Zootaxa, 2012)
The Indian region is presently the second region after the Neotropics in terms of diversity of phalangopsid crickets. Yet their study is impeded by the lack of necessary taxonomic tools for taxon identification. In the present paper, all generic diagnoses are clarified, using morphological and genitalic characters; female genitalia are described and illustrated for all genera with known females. New taxa are described from southern India: Kempiola flavipunctatus Desutter-Grandcolas n. sp., Opiliosina meridionalis Desutter-Grandcolas n. gen., n. sp., Phalangopsina bolivari Desutter-Grandcolas n. sp., P. chopardi Desutter-Grandcolas n. sp., P . gravelyi Desutter-Grandcolas n. sp., and Speluncasina Desutter-Grandcolas n. gen. The list of phalangopsid crickets from the Indian Region is updated, and a key to phalangopsid genera proposed. A lectotype and a paralectotype are designated to fix the name of Phalangopsina dubia (Bolivar, 1900). Opilionacris annandalei Chopard, 1928, previously transferred to the African genus Phaeophilacris Walker, 1871, is transferred to the genus Speluncasina Desutter-Grandcolas n. gen., while Larandopsis jharnae Bhowmik, 1981 and L. newguineae Bhowmik, 1981 described from New Guinea are transferred to the eneopterine genus Lebinthus Stål, 1877. Finally Luzaropsis confusa Chopard, 1969 is removed from its synonymy with L. ferruginea Walker, 1871.